2017
DOI: 10.24034/j25485024.y2015.v19.i1.1754
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Struktur Modal Dan Nilai Perusahaan Pertambangan Pasca Uu Nomor 4 Tahun 2009

Abstract: ABSTRAKTujuan penelitian yaitu mengetahui pengaruh profitabilitas, ukuran perusahaan, pertumbuhan perusahaan, risiko bisnis, kepemilikan manajerial, dan kepemilikan institusional terhadap struktur modal serta pengaruh struktur modal terhadap nilai perusahaan pertambangan pasca penerapan UU Nomor 4 Tahun 2009 tentang Pertambangan Mineral dan Batubara. Jenis penelitian merupakan penelitian hypothesis testing, yaitu penelitian yang dilakukan untuk menguji hipotesis berdasarkan kajian teoritis dan empiris. Populas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 22 publications
(26 reference statements)
4
5
0
1
Order By: Relevance
“…So high managerial ownership leads managers to make decisions to use low debt costs. This statement is in accordance with the research by Hasan and Butt (2009) and Sumani (2012) which states that the higher the managerial ownership, the lower the capital structure level. H1: Managerial ownership has a significant negative effect on capital structure.…”
Section: Hypotheses Developmentsupporting
confidence: 91%
See 1 more Smart Citation
“…So high managerial ownership leads managers to make decisions to use low debt costs. This statement is in accordance with the research by Hasan and Butt (2009) and Sumani (2012) which states that the higher the managerial ownership, the lower the capital structure level. H1: Managerial ownership has a significant negative effect on capital structure.…”
Section: Hypotheses Developmentsupporting
confidence: 91%
“…According to Hasan and Butt (2009), managerial ownership has negative effect against the capital structure, the big amount of debt increases bankruptcy risk so that high managerial ownership causes the managers to reduce the level of debt. The study is in line with Sumani (2012) which found a significant negative effect on the relationship between managerial ownership against the capital structure. It means that high managerial ownership will reduce the amount of debt used by the company.…”
Section: Introductionsupporting
confidence: 87%
“…Higher profitability can also be a signal regarding the potential decline in the use of external funds. This is supported by the research of Santika and Sudiyatno (2011), Murhadi (2011), Sari et al (2013), Chen et al (2013), Gomez et al (2014) Chadha andSharma (2015), Sumani (2015), Chipeta and Deressa (2015), Sofat and Singh (2016), Nur and Siahaan (2016), who found that the greater the profitability of the company, the less likely the company is to borrow debt. Profitability is measured by using the ratio of net income to total assets (ROA).…”
mentioning
confidence: 75%
“…So the amount of debt owned must be optimal so that the value of the company does not decrease. Mahendra et al (2012), Sari et al (2013), Hermuningsih (2013, Sumani (2015), Nguyen (2015), Osazuwa and Che-Ahmad (2015), Mangondu and Diantimala (2016), Ho and Ellis (2017), Anggriawan et al (2017), and Ibhagui and Olokoyo (2018) also find that an increased capital structure will decrease firm value, so the hypothesis is formulated as follows: Ha6: Capital structure has a negative effect on firm value.…”
mentioning
confidence: 99%
“…Perusahaan besar akan lebih mudah untuk memperoleh dana dari pasar modal. Hasil penelitian ini mendukung temuan penelitian Chandra (2017), Lim (2012), Sumani (2015). Namun, temuan penelitian tidak mendukung temuan penelitian Fachrudin (2013), Hardiyanto (2013), Acaravci (2015).…”
Section: Pengaruh Profitabilitas Terhadap Struktur Modalunclassified